Polypropylene composite material as well as preparation method and application thereof
By selecting a proportion of components in polypropylene composite materials and using specific compatibility agents, the plug -in or peeling structure is formed, the problem of poor heat -resistant deformation of polypropylene is solved, and the high bending modulus and excellent heat resistance are realized. Polyetric composite material.
Patent Information
- Application Number
- CN202411649994.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-24
AI Technical Summary
Polypropylene has poor heat deformation resistance under high loads, and it is difficult to achieve excellent performance in the preparation of existing polypropylene nanomaterials, mainly because the material is difficult to form intercalation or peeling structures in nanofillers.
By selecting the proportional proportion of polypropylene, polyzenzene ether, and modified mask, and use polypropylene closer clotherene and polypropylene closer losen anhydride as a compatible agent to form a polypropylene composite material Layer or stripping structure.
The high bending modulus and excellent heat resistance of polypropylene composite materials are realized. The amount of curvature is above 3120MPa and the thermal deformation temperature is above 164 ° C.
Smart Images

Figure BDA0005140659610000061 
Figure BDA0005140659610000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer engineering plastics, and in particular relates to a polypropylene composite material and a preparation method and application thereof. Background Art
[0002] Polypropylene is a crystalline compound with excellent oil resistance, solvent resistance and processing fluidity, but poor heat deformation resistance under high load and easy to warp. Polypropylene nanomaterials can better solve the problems of polypropylene, but the preparation of polypropylene nanomaterials has always been difficult to achieve. The reason is largely due to the non-polar properties of polypropylene, which makes it difficult for the material to form intercalation or exfoliation structures in nanofillers, thus making it impossible to achieve the excellent performance of nanomaterials. The polypropylene nanocomposites that can be achieved at present are also mainly intercalation structures, and the content of intercalation structures is also very limited, which has limited improvement on the mechanical properties and heat deformation resistance of polypropylene itself. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a polypropylene composite material that can realize an intercalation structure or a peeling structure between polypropylene and modified montmorillonite, and has a high flexural modulus and good heat resistance, as well as a preparation method and application thereof.
[0004] To achieve the above object, in a first aspect of the present invention, the present invention provides a polypropylene composite material, wherein the polypropylene composite material comprises the following components in parts by weight:
[0005] 58-82 parts of polypropylene (PP), 8-32 parts of polyphenylene ether (PPE), 6-22 parts of compatibilizer, 2-6 parts of montmorillonite;
[0006] The compatibilizer includes polypropylene grafted styrene (PP-g-St) and polypropylene grafted maleic anhydride (PP-g-MAH);
[0007] The grafting rate of the polypropylene grafted with styrene is ≥10%, and the grafting rate of the polypropylene grafted with maleic anhydride is ≥1.2%.
[0008] A polypropylene composite material provided by the present invention is compounded by selecting specific components in appropriate mass parts, and in the obtained polypropylene composite material, polypropylene and polyphenylene ether can form an intercalation structure or a stripping structure in montmorillonite, thereby effectively achieving the excellent performance of the polypropylene composite material, and the obtained polypropylene composite material has a high bending modulus and excellent thermal stability. Specifically, on the one hand, the present invention selects polypropylene and polyphenylene ether in an appropriate mass range, and the compounding of the two can effectively improve the bending modulus and thermal stability of the prepared product; on the other hand, the present invention selects polypropylene grafted styrene and polypropylene grafted maleic anhydride in an appropriate grafting rate range for compounding, which can significantly increase the compatibility between the non-polar polypropylene and polyphenylene ether alloy system and the polar system modified montmorillonite, and achieve an excellent volume expansion effect, thereby realizing the intercalation structure or stripping structure of the polypropylene composite material, and obtaining a higher bending modulus and good heat resistance.
[0009] The grafting rate of polypropylene grafted with styrene is tested by infrared spectrometer.
[0010] The grafting rate of polypropylene grafted with maleic anhydride is tested by acid-base titration method.
[0011] In the polypropylene composite material, the mass percentage of polypropylene is ≥49%.
[0012] Preferably, in the polypropylene composite material, the mass percentage of polypropylene is 55-78%.
[0013] For example, the weight percentage of the polypropylene may be any point value or any range value between 58 and 82 parts, such as 60 to 80 parts, or 58, 60, 62, 64, 66, 68, 70, 72, 74, 76, 78, 80, 82, etc.; the weight percentage of the polyphenylene ether may be any point value or any range value between 8 and 32 parts, such as 10 to 30 parts, or 8, 10, 12, 14, 16, 18, 20, 22 parts. , 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, etc.; the compatibilizer can be any point value or any two point range value between 6-22 parts, for example, it can be 8-20 parts, or it can be 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, etc.; the montmorillonite can be any point value or any two point range value between 2-6 parts, for example, it can be 2.5-5.5 parts, or it can be 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, etc.
[0014] Exemplarily, the grafting rate of polypropylene grafted styrene can be any point value or any two point range value between ≥10%, for example, it can be 10-15%, 10-18%, 10-12%, 15-18%, etc., or it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, etc.
[0015] Exemplarily, the grafting rate of the polypropylene grafted maleic anhydride can be any point value or any two point range value between ≥1.2%, for example, it can be 1.2-1.8%, 1.2-2.0%, 1.4-1.8%, etc., or it can be 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, etc.
[0016] Preferably, the grafting rate of polypropylene grafted with styrene is 12-15%.
[0017] Preferably, the grafting rate of maleic anhydride grafted onto polypropylene is 1.4-1.8%.
[0018] The present invention has found that the grafting rates of polypropylene grafted styrene and polypropylene grafted maleic anhydride will affect the compatibility between the alloy system and the modified montmorillonite. Only within the range of the compatibilizer type and grafting rate given by the present invention can the effective capacity increase of the two be achieved, thereby achieving an excellent comprehensive effect.
[0019] It should be noted that the polypropylene grafted styrene used in the present invention can be purchased from the market or prepared at home. If prepared at home, conventional preparation processes can be used.
[0020] For example, the preparation method of the polypropylene grafted styrene can adopt a melt grafting method, a solid phase radiation grafting method, a monomer polymerization method, etc.
[0021] As a preferred embodiment of the polypropylene composite material of the present invention, in the compatibilizer, the mass ratio of polypropylene grafted styrene to polypropylene grafted maleic anhydride is 1:(0.3-3.5).
[0022] Exemplarily, in the compatibilizer, the mass ratio of polypropylene grafted styrene and polypropylene grafted maleic anhydride can be any point value or any two point range values between 1:(0.3-3.5), such as 1:0.3, 1:0.5, 1:0.7, 1:0.9, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:18, 1:2, 1:2.5, 1:3.0, 1:3.5, etc.
[0023] Preferably, in the compatibilizer, the mass ratio of polypropylene grafted styrene to polypropylene grafted maleic anhydride is 1:(0.6-1.4).
[0024] The present invention has found that the mass ratio of polypropylene grafted styrene to polypropylene grafted maleic anhydride in the compatibilizer will affect the compatibility of the system, thereby affecting the structure, bending modulus and heat resistance of the product. When the mass ratio of polypropylene grafted styrene to polypropylene grafted maleic anhydride is further selected to be 1: (0.3-3.5), especially 1: (0.6-1.4), the comprehensive performance of the obtained product is better.
[0025] As a preferred embodiment of the polypropylene composite material of the present invention, the montmorillonite is a modified montmorillonite. The modified montmorillonite can be acid-modified, sodium-modified, inorganic salt-modified, long-chain quaternary ammonium salt-modified, amine compound-modified, etc. Among them, the modifying material that can be used in the acid modification includes any one of sulfuric acid, hydrochloric acid, phosphoric acid or their mixed acids; the modifying material used in the sodium modification includes any one of sodium chloride ethanol solution, sodium carbonate, sodium pyrophosphate, and sodium polyphosphate; the modifying material used in the inorganic salt modification includes any one of aluminum salt, magnesium salt, zinc salt, and copper salt; the modifying material used in the long-chain quaternary ammonium salt modification includes any one of 16-18 carbon amino ammonium salt or di-16-18 carbon alkyl ammonium salt; the modifying material used in the amine compound modification includes any one of primary amine and secondary amine.
[0026] Preferably, the modifier of the modified montmorillonite is any one of sodium carbonate, octadecyl methyl glycol salt and dioctadecyl dimethyl salt.
[0027] The present invention has found that the modification method of modified montmorillonite will affect the formation of the exfoliation structure or intercalation structure of the prepared product, thereby affecting the bending modulus and heat resistance of the prepared product. When the modified montmorillonite is selected as the above type, the comprehensive performance of the obtained product is better.
[0028] As a preferred embodiment of the polypropylene composite material of the present invention, the melt mass flow rate of the polypropylene at 230° C. / 2.16 kg is 60-75 g / 10 min.
[0029] It should be noted that the melt mass flow rate of polypropylene is obtained by testing at 230°C / 2.16kg with reference to ISO 1133-1:2022.
[0030] Exemplarily, the melt mass flow rate of the polypropylene at 230°C / 2.16kg may be any point value or any two point range values between 60-75g / 10min, such as 60g / 10min, 65g / 10min, 70g / 10min, 75g / 10min, etc.
[0031] As a preferred embodiment of the polypropylene composite material of the present invention, the intrinsic viscosity of the polyphenylene ether is 0.28-0.35 dl / g.
[0032] It should be noted that the intrinsic viscosity of polyphenylene ether is obtained by testing according to the intrinsic viscosity method in "GB / T41874-2022 Plastic Polyphenylene Ether (PPE) Resin".
[0033] Exemplarily, the intrinsic viscosity of the polyphenylene ether may be any point value or any two point range values between 0.28-0.35 dl / g, such as 0.28 dl / g, 0.29 dl / g, 0.30 dl / g, 0.31 dl / g, 0.32 dl / g, 0.33 dl / g, 0.34 dl / g, 0.35 dl / g, etc.
[0034] The present invention has found that when the melt mass flow rate of polypropylene and the intrinsic viscosity of polyphenylene ether are further selected within the above ranges, processing can be better achieved and a product with excellent comprehensive effects can be obtained.
[0035] In the second aspect of the present invention, the present invention also provides a method for preparing the polypropylene composite material, which comprises the following steps: weighing the dried raw materials, mixing them and feeding them into a twin-screw extruder, extruding, drawing, cooling, pelletizing and drying to obtain the polypropylene composite material.
[0036] As a preferred embodiment of the preparation method of the present invention, the parameters of the twin-screw extruder are: the aspect ratio of the twin-screw extruder is (25-35):1, the screw speed is 400-600rpm, and the extrusion temperature is 170-190°C.
[0037] In the third aspect of the present invention, the present invention also provides the use of the polypropylene composite material in the preparation of automobiles, household appliances, electronic and electrical engineering, and construction fields.
[0038] For example, polypropylene composite materials are used in the preparation of automobile door panels, automobile instrument panels, air-conditioning panels, air-conditioning outdoor unit grilles, electric control boxes, board room brackets and other materials.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The polypropylene composite material provided by the present invention is compounded by selecting specific components of appropriate mass parts, and in the obtained polypropylene composite material, polypropylene and polyphenylene ether can form an intercalation structure or even a peeling structure in the modified montmorillonite, thereby effectively achieving the excellent performance of the polypropylene composite material, and the obtained polypropylene composite material has a high tensile modulus and a high heat deformation temperature; specifically, the obtained product is a peeling structure or an intercalation structure, the bending modulus is above 3120MPa, and the heat deformation temperature is above 164°C. In addition, the preparation method of the polypropylene composite material provided by the present invention is simple to operate and is conducive to actual production. DETAILED DESCRIPTION
[0041] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0042] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0043] PP-1: EP648U, melt mass flow rate 62g / 10min, Sinochem Refining & Chemical;
[0044] PP-2: MN70, melt mass flow rate 70g / 10min, Yanshan Petrochemical;
[0045] PPE-1: SA9000, intrinsic viscosity 0.30 dl / g, Saudi Basic Industries Corporation;
[0046] PPE-2: TECANYL DRO, intrinsic viscosity 0.33 dl / g, Ensinger Chemical;
[0047] PA6: M2400, intrinsic viscosity 0.35dl / g, Xinhui Meida;
[0048] PP-g-St-1: grafting rate 12%, homemade;
[0049] PP-g-St-2: grafting rate 15%, homemade;
[0050] PP-g-St-3: 1616FA, grafting rate 10%, BYK chemistry;
[0051] PP-g-St-4: grafting rate 18%, homemade;
[0052] PP-g-St-5: grafting rate is 8%, homemade;
[0053] PP-g-MAH-1: 8112FA, grafting rate 1.4%, BYK chemistry;
[0054] PP-g-MAH-2: 9212FA, grafting rate 1.8%, BYK chemistry;
[0055] PP-g-MAH-3: 2112GA, grafting rate 1.2%, BYK chemistry;
[0056] PP-g-MAH-4: 10213, grafting rate 2.0%, BYK chemistry;
[0057] PP-g-MAH-5: 1001CN, grafting rate 1%, Bondyram;
[0058] Modified montmorillonite 1: PGN, modifier is sodium carbonate, NANOCOR;
[0059] Modified montmorillonite 2: I.34T, the modifier is octadecyl methyl glycolate, NANOCOR;
[0060] Modified montmorillonite 3: I.44P, the modifier is dioctadecyl dimethyl salt, NANOCOR.
[0061] Among them, the homemade method of PP-g-St adopts a melt grafting method, which includes the following steps: using 0.5%wt of benzoyl peroxide, dissolving a certain amount of styrene (such as 8%, 12%, 15%) in acetone, adding polypropylene (PP 320, the melt mass flow rate at 230°C / 2.16kg is 30g / 10min), stirring fully and then adding it into a twin-screw extruder, controlling the temperature at 160-200°C, the main engine speed at 120rpm, and the feeding screw speed at 20rpm; PP-g-St is obtained; PP-g-St with different grafting rates is achieved by controlling the amount of styrene added.
[0062] Examples 1-14 and Comparative Examples 1-7
[0063] The embodiments and comparative examples of the present invention provide a polypropylene composite material, and the component contents (parts by weight) of the polypropylene composite material are shown in Tables 1-3;
[0064] Table 1
[0065] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 PP-1 67 60 80 / 67 67 67 67 PP-2 / / / 67 / / / / PPE-1 20 10 30 / 20 20 20 20 PPE-2 / / / 20 / / / / PP-g-St-1 8 3 12 8 3.7 12.3 8 8 PP-g-MAH-1 8 5 8.6 8 12.3 3.7 8 8 Modified montmorillonite 1 3 2.5 5.5 3 3 3 / / Modified montmorillonite 2 / / / / / / 3 / Modified montmorillonite 3 / / / / / / / 3
[0066] Table 2
[0067]
[0068]
[0069] Table 3
[0070] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 PP-1 87 20 67 67 67 67 67 PPE-1 / 67 20 20 20 20 / PA6 / / / / / / 20 PP-g-St-1 8 8 16 / / 8 8 PP-g-St-5 / / / / 8 / / PP-g-MAH-1 8 8 16 8 / 8 PP-g-MAH-5 / / / / / 8 / Modified montmorillonite 1 3 3 3 3 3 3 3
[0071] The preparation method of the polypropylene composite material provided in Example 1 is:
[0072] The dried raw materials are weighed, mixed and fed into a twin-screw extruder, and subjected to extrusion, stranding, cooling, pelletizing and drying to obtain a polypropylene composite material;
[0073] The parameters of the twin-screw extruder are as follows: the aspect ratio of the twin-screw extruder is 30:1, the screw speed is 500 rpm, and the extrusion temperature is 180°C.
[0074] The preparation methods of the polypropylene composite materials provided in Examples 2-14 and Comparative Examples 1-7 are consistent with that in Example 1, except that no relevant components are added.
[0075] Effect example
[0076] The effect examples of the present invention verify the performance of the products prepared in the embodiments and comparative examples; the test items include the following aspects:
[0077] 1. Interlamellar spacing: The test standard refers to ASTM D934-2013, and the instrument is X'Pert PRO diffractometer. After XRD testing, the interlamellar spacing d is calculated according to the Bragg formula (Bragg formula nλ=2dsinθ), where n=1 (first-order diffraction), λ is the wavelength of the x-ray, and θ is the readout of the XRD test result; if the interlamellar spacing tested cannot be detected, it means that the product is a completely peeled structure;
[0078] 2. Flexural modulus: The test standard is tested in accordance with ISO 178-2019;
[0079] 3. Heat deformation temperature: The test standard is based on ISO 75-2:2013, and the test load pressure is 0.45MPa;
[0080] The test results are shown in Table 4;
[0081] Table 4
[0082] Interlamellar spacing / nm Flexural modulus / MPa Heat deformation temperature / ℃ Example 1 / 3550 172 Example 2 18.9 3120 168 Example 3 18.1 3530 169 Example 4 / 3545 171 Example 5 19.1 3482 167 Example 6 19.3 3441 166 Example 7 / 3572 173 Example 8 19.2 3488 169 Example 9 / 3601 172 Example 10 19.2 3448 168 Embodiment 11 19.1 3460 169 Example 12 / 3548 171 Example 13 18.9 3440 165 Embodiment 14 18.8 3432 164 Comparative Example 1 0.8 1600 128 Comparative Example 2 1.5 1980 128 Comparative Example 3 0.6 1578 115 Comparative Example 4 0.5 1540 113 Comparative Example 5 7.4 2040 132 Comparative Example 6 8.6 2053 138 Comparative Example 7 0.7 1624 125
[0083] It can be seen from Table 4 that when the technical solution of the present invention is adopted, the obtained products can form a peeling structure or an intercalation structure, and the interlamellar spacing is above 18.1 nm, and even the spacing cannot be measured in part, that is, a completely peeling structure, and the obtained products have a higher bending modulus and better heat resistance. Specifically, the bending modulus of the obtained product is above 3120 MPa, and the heat deformation temperature is above 164°C;
[0084] It can be seen from Examples 1-3 and Comparative Example 1 that when PPE is not added to the system of Comparative Example 1, the flexural modulus and heat resistance of the obtained product are significantly reduced; it can be seen from Examples 1-3 and Comparative Example 2 that the mass parts of the components have a significant effect on the performance of the product. When the mass parts of the components in Comparative Example 2 are not within the range given in the present invention, the flexural modulus and heat resistance of the obtained product are significantly reduced; it can be seen from Example 1 and Comparative Example 7 that when other substances are used to replace PPE, the obtained product cannot achieve the high flexural modulus and excellent heat resistance of the present invention;
[0085] It can be seen from Example 1 and Examples 5-6 that, when the total number of compatibilizers is kept the same, the mass ratio of polypropylene grafted styrene and polypropylene grafted maleic anhydride will also affect the comprehensive performance of the product. When the mass ratio of the two is further selected within the preferred range, the flexural modulus and heat deformation temperature of the obtained product are higher. It can be seen from Example 1 and Comparative Examples 3-4 that when the number of compatibilizers is kept unchanged, but only any one of the compatibilizers is added, the comprehensive performance of the obtained product is significantly reduced.
[0086] It can be seen from Example 1 and Examples 7-8 that the interlamellar spacing of the modified montmorillonite will also affect the comprehensive performance of the product. When the interlamellar spacing of the modified montmorillonite is further selected to be within the preferred range of the present invention, the comprehensive effect of the obtained product is better.
[0087] It can be seen from Example 1, Examples 10-14 and Comparative Examples 5-6 that the grafting rates of polypropylene grafted styrene and polypropylene grafted maleic anhydride used in the present invention have a significant impact on the results. When the grafting rates of polypropylene grafted styrene and polypropylene grafted maleic anhydride in Comparative Examples 5-6 are not within the range given in the present invention, the compatibility of the system cannot be effectively improved, and the bending modulus and heat deformation temperature of the obtained product both show a significant downward trend; when the grafting rates of polypropylene grafted styrene and polypropylene grafted maleic anhydride are further selected to be within the preferred range of the present invention, the comprehensive performance of the obtained product is better.
[0088] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polypropylene composite material, characterized in that: The polypropylene composite material comprises the following components in parts by weight: 58-82 parts of polypropylene, 8-32 parts of polyphenylene ether, 6-22 parts of compatibilizer, 2-6 parts of montmorillonite; The compatibilizer includes polypropylene grafted styrene and polypropylene grafted maleic anhydride; The grafting rate of the polypropylene grafted with styrene is ≥10%, and the grafting rate of the polypropylene grafted with maleic anhydride is ≥1.2%.
2. The polypropylene composite material according to claim 1, characterized in that: The grafting rate of polypropylene grafted with styrene is 12-15%.
3. The polypropylene composite material according to claim 1, characterized in that: The grafting rate of maleic anhydride grafted onto polypropylene is 1.4-1.8%.
4. The polypropylene composite material according to claim 1, characterized in that: In the compatibilizer, the mass ratio of polypropylene grafted styrene to polypropylene grafted maleic anhydride is 1:(0.3-3.5).
5. The polypropylene composite material according to claim 1, characterized in that: The montmorillonite is modified montmorillonite, and the modifier of the modified montmorillonite is any one of sodium carbonate, octadecyl methyl glycol salt, and dioctadecyl dimethyl salt.
6. The polypropylene composite material according to claim 1, characterized in that: The melt mass flow rate of the polypropylene at 230° C. / 2.16 kg is 60-75 g / 10 min.
7. The polypropylene composite material according to claim 1, characterized in that: The intrinsic viscosity of the polyphenylene ether is 0.28-0.35 dl / g.
8. The method for preparing the polypropylene composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: weighing the dried raw materials, mixing them and sending them into a twin-screw extruder, extruding, drawing, cooling, pelletizing and drying to obtain a polypropylene composite material.
9. Use of the polypropylene composite material according to any one of claims 1 to 7 in the preparation of automobiles, household appliances, electronic and electrical engineering, and construction fields.
Citation Information
Cited By
PP composite material and preparation method and application thereof
CN120157987A
Resin composition, prepreg, resin-coated film, resin-coated metal foil, metal-clad laminate, and wiring board
US20240182657A1